(untitled) (El Hilo de la Fabula, 2021)
Thinking, like Minerva’s owl, spreads its wings only with the falling of dusk. Whereas for Hegel, this was a proof of wisdom, now it only indicates failure: facts explode in his face. Philosophy and criticism, with a few exceptions, still argue that there are only «consensual fictions» (Rancière 2008) or, as Alain Badiou denounces, that «there are only bodies and languages» (Badiou 2008:621). Psychoanalysis, science and art, instead, have been able to imagine catastrophe with ease for a long time, and a kind of realism capable of recovering the ethical tension in the sense of change (Gramuglio) will be the one that thinks and signals the hesitation of fictions towards the real. In Pongamos por caso (2020), structured by Rafael Spregelburd and riddled by delegated performances of translators, the playwright «makes an accomplice out of the spectator of the fact that he is witnessing an act, despite it being traversed by states of truth. And that is what is real» (Spregelburd 2010:170-171).